VITrti : 2 juni - 26 oktober 2007 - Verbeke, Geert; Uit den Bogaard, Martin; Tentoonstelling. Kemzeke. Verbeke Foundation. 2007-06, 02 (Kemzeke : Verbeke Foundation, 2007)
Angeloni, Franco ; De Beer, Geoffrey ; Bernier, Pascal ; De Bie, Annie ; Bloom, Phil ; uit den Bogaard, Martin ; Bolink, Merijn ; Van Braak, Kevin ; Van Breedam, Camiel ; Brendel, Micha ; De Bruyckere, Berlinde ; De Bruyn, Goele ; Buggenhout, Peter ; Buisman, Sjoerd ; Castelyns, Frank F. ; Claessens, Roger ; Coolen, Caroline ; Copers, Leo ; De Cupere, Peter ; d'O, Honoré ; Deguislage, Delphine ; Delvoye, Wim ; Dick, Helmut ; van Dijck, Bart ; Ebinger, Moritz ; Fabre, Jan ; François, Michel ; Happy Famous Artists ; Heirmans, Harry ; Idiots ; ILAP ; Jeannin, Lisa ; Khun, Joe ; Korstanje, Maartje ; Kuster, Jeroen ; Kuyl, Chiel ; Lagendijk, Reinier ; van Lieshout, Joep ; Likely, Seymour ; Linares, Michael ; Manje, Sarah ; Martin, Kris ; Meijman, Sjef ; Mich, Ludo ; Morris, Desmond ; Van Nazareth, Herman ; Rombouts, Guy ; Ross, Liron ; Schuurmans, Rolf ; Servaas ; Smeenge, Kor ; Smits, Helmut ; Spee, Renate ; Startel ; Tratnik, Polona ; Ulrichs, Timm ; Vanhemelrijck, Kris ; Vanmechelen, Koen ; Wenners, Julia ; De Winter, Ronald
Tentoonstelling 2 juni - 26 oktober 2007
Gift An Van Dienderen
boek